Peranan Wakaf Menurut Mazhab Syafi'i Dalam Mengurangkan Kemiskinan Di Brunei Darussalam - Harnee Sehwana Binti Amdani; Dr. Hajah Mas Nooraini Binti Haji Mohiddin; Fitriana Nur Annisa (Islamic Economic Law Programs, Faculty of Sharia and Law, UIN Sunan Ampel Surabaya, 2025)
Abstract: Waqf is seen as an Islamic economic tool that has great potential in helping poor groups as well as providing employment opportunities. In the Syafi’i School, waqf is considered a charity whose benefits are sustainable, not only from a religious perspective, but also in socio-economic development. Data shows that the unemployment rate in Brunei Darussalam in 2023 will reach 5.1%, with 44.3% of the poor population consisting of unemployed individuals. This condition makes waqf an important tool in providing sustainable employment. Using qualitative and quantitative approaches, this investigation analyzes fiqh books, academic journals, and secondary data relating to poverty and unemployment in Brunei. In addition, surveys and interviews were carried out with the Brunei Islamic Religious Council (MUIB) and the Zakat, Waqf and Baitulmal Affairs Department (JUZWAB) to gain an understanding of the challenges and possibilities that arise in managing waqf. The research findings indicate that productive waqf, cash waqf, and educational waqf can be sustainable solutions to reduce poverty and unemployment, emphasizing the role of JUZWAB in more effective waqf management and distribution. Despite challenges such as low public awareness and suboptimal waqf asset management, this study recommends policy and management improvements to maximize the impact of waqf on socio-economic development in Brunei Darussalam. Keywords: Waqf, Shafi’i School, Poverty, Brunei Darussalam. Abstrak: Wakaf dilihat sebagai alat ekonomi Islam yang memiliki potensi besar dalam membantu kelompok miskin sekaligus menyediakan lapangan kerja. Dalam Mazhab Syafi’i, wakaf dianggap sebagai amal jariyah yang manfaatnya berkelanjutan, tidak hanya dari segi keagamaan, tetapi juga dalam pembangunan sosial-ekonomi. Data menunjukkan bahwa tingkat pengangguran di Brunei Darussalam pada tahun 2023 mencapai 5,1%, dengan 44,3% dari populasi miskin terdiri atas individu yang tidak bekerja. Kondisi ini menjadikan wakaf sebagai alat penting dalam penyediaan lapangan kerja yang berkesinambungan. Menggunakan pendekatan kualitatif dan kuantitatif, penyelidikan ini menganalisis kitab-kitab fikih, jurnal akademik, dan data sekunder yang berkaitan dengan kemiskinan dan pengangguran di Brunei. Selain itu, dijalankan survei dan wawancara dengan Majelis Ugama Islam Brunei (MUIB) serta Jabatan Urusan Zakat, Wakaf, dan Baitulmal (JUZWAB) untuk mendapatkan pemahaman tentang cabaran dan kemungkinan yang timbul dalam pengurusan wakaf. Hasil penelitian menunjukkan bahwa wakaf produktif, wakaf tunai, dan wakaf pendidikan dapat menjadi solusi berkelanjutan dalam mengurangi kemiskinan dan pengangguran, dengan menekankan peran JUZWAB dalam pengelolaan dan distribusi wakaf yang lebih efektif. Meskipun terdapat tantangan seperti rendahnya kesadaran masyarakat dan pengelolaan aset wakaf yang belum optimal, penelitian ini merekomendasikan adanya perbaikan kebijakan dan manajemen guna memaksimalkan dampak wakaf terhadap pembangunan sosial-ekonomi di Brunei Darussalam. Kata Kunci: Wakaf, Mazhab Syafi’i, Kemiskinan, Brunei Darussalam.